2003
DOI: 10.1002/chem.200204447
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Energetics in Alkaline Metal Alkoxides and Phenoxides

Abstract: The bonding energetics in a variety of alkaline metal, alkoxides and phenoxides, MOR, was investigated based on the corresponding enthalpies of formation in the crystalline state determined by reaction-solution calorimetry. The results obtained at 298.15 K were as follows: Delta(f)H(m)(o)(MOR, cr)/kJ mol(-1) = 382.7+/-1.4 (LiOC(6)H(5)), 513.6+/-2.5 (NaO-nC(6)H(13)), 326.4+/-1.4 (NaOC(6)H(5)), 375.2+/-3.4 (KOCH(3)), 434.5+/-2.7 (KOC(2)H(5)), 467.1+/-5.2 (KO-nC(3)H(7)), 459.3+/-2.1 (KO-nC(4)H(9)), 464.6+/-5.7 (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…It was found that using CsHMDS as the base greatly accelerated the rate of the reaction, relative to other alkali-metal cations . One possible explanation for the significant counterion effect is that the rate of elimination from Cp* 2 Zr(O – X + )OTf is dependent on the counterion, with the weaker ionic bond between [Zr]–O – and Cs + leading to faster reaction rates . Alternatively, as the elimination reaction is heterogeneous, the Cs cation may have increased solubility and therefore faster reaction rates .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that using CsHMDS as the base greatly accelerated the rate of the reaction, relative to other alkali-metal cations . One possible explanation for the significant counterion effect is that the rate of elimination from Cp* 2 Zr(O – X + )OTf is dependent on the counterion, with the weaker ionic bond between [Zr]–O – and Cs + leading to faster reaction rates . Alternatively, as the elimination reaction is heterogeneous, the Cs cation may have increased solubility and therefore faster reaction rates .…”
mentioning
confidence: 99%
“…12 One possible explanation for the significant counterion effect is that the rate of elimination from Cp* 2 Zr(O − X + )OTf is dependent on the counterion, with the weaker ionic bond between [Zr]−O − and Cs + leading to faster reaction rates. 13 Alternatively, as the elimination reaction is heterogeneous, the Cs cation may have increased solubility and therefore faster reaction rates. 14 The subsequent carbonyl insertion into p-trifluoromethylbenzaldehyde occurs cleanly at room temperature to afford the dioxazirconacyclohexene 3a quantitatively, as determined by 1 H NMR, and was isolated in 99% yield as a yellow solid.…”
mentioning
confidence: 99%
“…The values of thermochemical radii, OPh À , in alkaline-metal phenoxides were recalculations of data using auxiliary values [21]. Values of thermochemical radii, 2,6-Me 2 OPh À for alkaline-metal phenoxides were determined in a previous work [20].…”
Section: Calorimetric Measurementsmentioning
confidence: 99%
“…15. The slope was taken from reference [21]; it was obtained by plotting d M-OC6H5 against (r + + r À ) data from alkaline phenoxide compounds. The second shell (Ca + Ca) is merely an assumption.…”
Section: Calorimetric Measurementsmentioning
confidence: 99%
“…10 The bonding energetics in a variety of alkali metal alkoxides and aryloxides have been determined using reaction-solution calorimetry and trends in the structureenergetics relationship, based on the Kapustinskii equation, were discussed. 11 The syntheses and unusual (in some cases unprecedented) structures of nine alkali metal amides derived from the [N(SiMe 2 Ph)(SiMe 3 )], [N(Bu t )(SiMe 3 )], [N(Ph)(2-C 5 H 4 N)] and [N(2-C 5 H 4 N) 2 ] anions have been reported. 12 A series of alkali metal 4-hydroxyphenolates and 1,4-phenylenediolates (hydroquinones) have been structurally characterized.…”
Section: Introductionmentioning
confidence: 99%